To Reconnect Natural Logarithm and Unit Circle

Calculus Level 5

A common tangent is drawn to the natural logarithm y = ln x b y=\dfrac{\ln x}{b} and the unit circle x 2 + y 2 = 1 x^2+y^2=1 , touching the natural logarithm at point A ( α , β ) A(\alpha, \beta) , where α ( b ) \alpha(b) is a function of b b . Find the following sum

315 b = 1 ( 1 ln ( α ( b ) ) 1 ) 2 \left\lfloor 315 \sum_{b=1}^{\infty} \left( \frac{1}{ \lfloor \ln (\alpha(b)) \rfloor -1}\right)^2 \right\rfloor

Notation: \lfloor\cdot\rfloor denotes the floor function .


The answer is 518.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Apr 29, 2019

The tangent to the logarithm curve y = ln x b y = \tfrac{\ln x}{b} at the point x = α x=\alpha has equation y ln α b = 1 b α ( x α ) b α y x = α ( ln α 1 ) \begin{aligned} y - \tfrac{\ln \alpha}{b} & = \; \tfrac{1}{b\alpha}(x-\alpha) \\ b\alpha y - x & = \; \alpha(\ln\alpha - 1) \end{aligned} and this will be tangent to the unit circle around the origin provided that the distance from it to the origin is 1 1 , so that α ( ln α 1 ) 1 + b 2 α 2 = 1 \frac{|\alpha(\ln \alpha - 1)|}{\sqrt{1 + b^2\alpha^2}} \; = \; 1 which implies that α 2 ( ln α 1 ) 2 = 1 + b 2 α 2 \alpha^2(\ln \alpha - 1)^2 \; = \; 1 + b^2\alpha^2 Regarding b b as a function of α \alpha , we see that b ( α ) > 0 b'(\alpha) > 0 for α > 3 \alpha > 3 , with b ( 3 ) = 0.101 b(3) = -0.101 . Moreover b ( α ) b(\alpha) \to \infty as α \alpha \to \infty . Thus we can certainly find a unique value α ( b ) > 3 \alpha(b) > 3 for any b 1 b\ge 1 . Since ( ln α ( b ) 1 ) 2 = b 2 + α ( b ) 2 (\ln\alpha(b) - 1)^2 \; = \; b^2 + \alpha(b)^{-2} we deduce that b 2 < ( ln α ( b ) 1 ) 2 < b 2 + 1 < ( b + 1 ) 2 b N b^2 \; < \; (\ln\alpha(b) - 1)^2 \; < \; b^2 + 1 \; < \; (b+1)^2 \hspace{2cm} b \in \mathbb{N} and hence b < ln α ( b ) 1 < b + 1 b < \ln\alpha(b) - 1 < b+1 for all positive integers b b , so that ln α ( b ) 1 = b \lfloor \ln\alpha(b)\rfloor - 1 = b for all positive integers b b . Thus 315 b = 1 1 ( ln α ( b ) 1 ) 2 = 315 b = 1 b 2 = 315 × 1 6 π 2 = 518 \left\lfloor 315\sum_{b=1}^\infty \frac{1}{(\lfloor\ln\alpha(b)\rfloor-1)^2}\right\rfloor \; = \; \left\lfloor 315 \sum_{b=1}^\infty b^{-2}\right\rfloor \; = \; \left\lfloor 315 \times \tfrac16\pi^2\right\rfloor \; = \; \boxed{518}

Thanks for the solution.

Kazem Sepehrinia - 2 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...